Wireless ad hoc and sensor networks theory and applications - Li, Xiang-Yang (Cambridge University Press, 2008)
If you have to understand and optimize the performance of wireless ad hoc and sensor networks, this explanation provides you with the information and insights you need. It delivers an understanding of the underlying problems, and the techniques to develop efficient solutions and maximize network performance. Taking an algorithmic and theoretical approach, Li dissects key layers of a wireless network, from the physical and MAC layers (covering the IEEE 802.11 and 802.16 protocols, and protocols for wireless sensor networks and Bluetooth) through to the network routing layer. In doing so he reviews the practical protocols, formulates problems mathematically, solves them algorithmically and then analyses the performance. Graduate students, researchers and practitioners needing an overview of the various algorithmic, graph theoretical, computational geometric and probabilistic approaches to solving problems in designing these networks will find this an invaluable resource. Additional resources for this title are available online at www.cambridge.org/9780521865234